Liver Abscess: A Case Report - I Nyoman Ika Prapta Swartawan; I Wayan Eka Saputra (HM Publisher, 2023)
A liver abscess is a form of infection in the liver, which is characterized by the presence of pus covered by fibrous tissue in the liver parenchyma. The two most common types of liver abscesses are pyogenic and amebic abscesses, which are usually found in the right lobe of the liver. This study aimed to report cases of liver abscesses that occurred in the left lobe of the liver, with non-specific complaints. The patient came with complaints of a swollen abdomen, pain in the upper right abdomen, and intermittent fever. Radiological examination in the form of a CT scan confirmed the diagnosis of a left lobe hepatic abscess. The patient was treated with an abscess drainase per laparotomy. No complications were found during and after surgery. Open abscess drainase by laparotomy combined with antibiotic therapy is a safe and effective therapeutic approach in such cases.